Enhanced mechanism of thermoelectric performance of Bi2Se3 using density functional theory - Muhammad Zamir Mohyedin; Mohamad Fariz Mohamad Taib; Afiq Radzwan; M. Mustaffa; Amiruddin Shaari; Oskar Hasdinor Hassan; Ab Malik Marwan Ali; Bakhtiar Ul Haq; Muhd Zu Azhan Yahya (Materials for Renewable and Sustainable Energy, 2020)
Abstract Good thermoelectric performance is being sought to face major problems related to energy, especially in the concern of the usage of energy on environmental impact. In this work, we investigate the underlying mechanism to enhance the thermoelectric performance of bismuth selenide (Bi2Se3) by employing density functional theory (DFT) followed by the Boltzmann transport equation under relaxation time approximation. The structural, electronic, and thermoelectric properties were calculated and analyzed. From the analysis of combined results of thermoelectric properties and electronic properties as the function of the Fermi level, we found that the power factor of Bi2Se3 is improved by increasing electrical conductivity that contributed by the large density of states and light effective mass of charge carriers. The figure of merit, on the other hand, is enhanced by increasing Seebeck coefficient that contributed by heavy effective mass and decreasing thermal conductivity that contributed by low density of states. We also found that both power factor and figure of merit can be improved through n-type doping at 300 K and p-type doping at higher temperature (400 K and 500 K).